Identification of Uncommon Cryptosporidiumviatorum (a Novel Subtype XVcA2G1c) and Cryptosporidium andersoni as Well as Common Giardia duodenalis Assemblages A and B in Humans in Myanmar - Wu, Yanchen; Gong, Baiyan; Liu, Xiaohua; Jiang, Yanyan; Cao, Jianping; Yao, Lan; Li, He; Liu, Aiqin; Shen, Yujuan (Frontiers in Cellular and Infection Microbiology, 2020)
Cryptosporidium and Giardia are two important zoonotic intestinal protozoa responsible for diarrheal diseases in humans and animals worldwide. Feces from infected hosts, water and food contaminated by Cryptosporidium oocysts and Giardia cysts as well as predictors such as poverty have been involved in their transmission. Myanmar is one of the world’s most impoverished countries. To date, there are few epidemiological studies of Cryptosporidium and Giardia in humans. To understand the prevalence and genetic characterization of Cryptosporidium spp. and Giardia duodenalis in humans in Myanmar, a molecular epidemiological investigation of the two protozoa was conducted in four villages of Shan State. 172 fecal specimens were collected from Wa people (one each) and identified for the presence of Cryptosporidium spp. and G. duodenalis by sequence analysis of their respective small subunit ribosomal RNA genes. 1.74% of investigated people were infected with Cryptosporidium spp.—C. andersoni (n = 2) and C. viatorum (n = 1) while 11.05% infected with G. duodenalis—assemblages A (n = 6) and B (n = 13). By sequence analysis of 60-kDa glycoprotein gene, the C. viatorum isolate belonged to a novel subtype XVcA2G1c. DNA preparations positive for G. duodenalis were further subtyped. Five of them were amplified and sequenced successfully: different assemblage B sequences (n = 2) at the triosephosphate isomerase (tpi) locus; sub-assemblage AII sequence (n = 1) and identical assemblage B sequences (n = 2) at the β-giardin (bg) locus. This is the first molecular epidemiological study of Cryptosporidium spp. and G. duodenalis in humans in Myanmar at both genotype and subtype levels. Due to unclear transmission patterns and dynamics of Cryptosporidium spp. and G. duodenalis, future research effort should focus on molecular epidemiological investigations of the two parasites in humans and animals living in close contact in the investigated areas, even in whole Myanmar. These data will aid in making efficient control strategies to intervene with and prevent occurrence of both diseases.